Rancang Bangun Sistem Informasi Wedding Planner Berbasis Website (Studi Kasus: Gema Gawita Planner & Decoration) - Rosadi, Reza Ghaniyy; Sylviana, Felicia; Saputra, Ade Chandra (Universitas Palangka Raya, 2023)
Marriage is the most sacred and main form of human relationship, so every couple will undoubtedly make total preparations to face the marriage. Gema Gawita Planner & Decoration is a company engaged in wedding planning where their job is to plan all wedding preparations from the beginning of planning until the wedding day arrives. The old system process in Gema Gawita Planner & Decoration is still done manually, which is somewhat less efficient. The system that will be designed can help Gema Gawita Planner & Decoration improve their performance & make it easier for potential customers to reach them. The methodology used in making the Wedding Planner Information System Website (Case Study: Gema Gawita Planner & Decoration) is waterfall, with the stages, namely the requirements definition stage described using a flowchart. Requirements analysis and definition is described through DFD (Data Flow Diagram, ERD (Entity Relationship Diagram) and database. Integration and system testing uses the blackbox testing method, blackbox testing is carried out directly by Gema Gawita Planner & Decoration where there are website test results that the website runs according to its function. On the Wedding Planner Information System Website (Case Study: Gema Gawita Planner & Decoration) there is profile information, vendor information, product information, wedding inspiration information, so that users can design their wedding budget where there is a recommendation system in it and users can schedule appointments. meeting with the vendor. The existence of this website system aims to provide information and facilitate the bride and groom in preparing their wedding planning.